2017
DOI: 10.3390/su9091528
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Waste Management Expenditure and Waste Reduction Targets on Selected JSE Companies

Abstract: Waste generation and waste management are critical environmental issues faced by countries all over the world. Furthermore, there are greater environmental, economic, and social demands on firms to reduce the environmental impacts due to environmental problems brought about by their operating activities. There is a current debate as to the financial implications of waste management expenditure on waste reduction targets. This study examines the relationship between waste management expenditure on waste reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Decreasing footprint is becoming a focal task of several firms since research has found that consumers are increasingly making purchase decisions led also by moral rationale and pro‐environmental motivation (Hoffmann & Hutter, 2012), confirming that the interest towards firm policies behind the products is rapidly growing (Grappi et al, 2017). Recent studies have also highlighted that consumers appreciate those firms that share information about their socially responsible activities (Griskevicius et al, 2010; Semmann et al, 2005), and good behavior towards the environment, such as commitment in reducing waste, could support firm in generating benefits that include improved firm's reputation (Maleka et al, 2017; Song et al, 2017). In fact, customers are more likely to acquire products from those firms they perceive as being environmentally responsible and that demonstrate to be compliant with sustainable principles (Grimmer & Bingham, 2013).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Decreasing footprint is becoming a focal task of several firms since research has found that consumers are increasingly making purchase decisions led also by moral rationale and pro‐environmental motivation (Hoffmann & Hutter, 2012), confirming that the interest towards firm policies behind the products is rapidly growing (Grappi et al, 2017). Recent studies have also highlighted that consumers appreciate those firms that share information about their socially responsible activities (Griskevicius et al, 2010; Semmann et al, 2005), and good behavior towards the environment, such as commitment in reducing waste, could support firm in generating benefits that include improved firm's reputation (Maleka et al, 2017; Song et al, 2017). In fact, customers are more likely to acquire products from those firms they perceive as being environmentally responsible and that demonstrate to be compliant with sustainable principles (Grimmer & Bingham, 2013).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…It is important to determine if other underlying factors have an influence on the dependent variable [ 75 ]. Hence, these factors should be tested prior to the independent variable to provide an alternate explanation for the findings.…”
Section: Methodsmentioning
confidence: 99%
“…The ordinary least squares model is one of the most common approaches to analyzing panel data, as evidenced in the literature (Maleka et al, 2017;Mukwarami & Fakoya, 2022). However, OLS has shortcomings that should be considered before relying on the results.…”
Section: Panel Data Estimatorsmentioning
confidence: 99%